THE EFFECT OF WORKLOAD AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE OF PT JASAMARGA KUALANAMU – TEBING TINGGI ROUTE - Putri Agustini Lubis; Rahmah Aina Az Zahra; Eka Mayastika Sinaga; Willy Cahyadi (RADJA PUBLIKA, 2025)
This study aims to determine how the workload and work motivation affect the performance of employees of PT Jasamarga Segment Kualanamu - Tebing Tinggi both partially and simultaneously. The approach of this study is associative. The population is all employees of PT Jasamarga Segment Kualanamu - Tebing Tinggi and the sample is 35 employees of PT Jasamarga Segment Kualanamu - Tebing Tinggi. The data collection technique in this study uses a questionnaire technique. The data analysis technique in this study uses Multiple Linear Regression Analysis Test, Hypothesis Test (t Test and F Test), and Coefficient of Determination. Data processing in this study uses SPSS (Statistical Package for the Social Sciences) software version 29.00. Partially there is a positive and significant effect between workload on employee performance of PT Jasamarga Segment Kualanamu - Tebing Tinggi. Partially there is a positive and significant effect between work motivation on employee performance of PT Jasamarga Segment Kualanamu - Tebing Tinggi. Simultaneously there is a positive and significant effect between workload and work motivation on employee performance of PT Jasamarga Segment Kualanamu - Tebing Tinggi.